Interpersonal Psychotherapy for Bereavement-Related Major Depressive Disorder in Japan: A Systematic Case Report - Toshishige, Yuko; Kondo, Masaki; Okazaki, Junya; Mizushima, Hiroko; Akechi, Tatsuo (Case Reports in Psychiatry, 2022)
Bereavement-related major depressive disorder (MDD) is a common disorder with both mental and physical effects. Specific psychotherapies for bereavement-related MDD remain unavailable in Japan despite its relatively high prevalence. Interpersonal psychotherapy (IPT) is a treatment with established efficacy for MDD, including bereavement-related MDD. There are, however, few studies of IPT for MDD and none at all for bereavement-related MDD in Japan. The efficacy of IPT for bereavement-related MDD needs confirmation in Japanese culture because the expression of emotions during the grieving and mourning process varies across cultures, and the Japanese-specific cultural custom exists of maintaining a relationship with the deceased in the afterlife mainly via a Buddhist memorial tablet, altar, and grave. We present a case study describing the therapist’s adaptation of IPT to Japanese culture to treat bereavement-related MDD in a Japanese man with insufficient response to pharmacotherapy who had suddenly lost his mother to heart disease. His mother’s death and a dispute with his father both appeared to have contributed to his sustained bereavement-related MDD. The 16-session treatment course for depressive symptoms was monitored using the Beck Depression Inventory-II. Treatment was scheduled weekly, but some sessions unavoidably took place fortnightly because they were conducted in person during the COVID-19 pandemic. The patient’s MDD severity continually decreased, functional disability gradually recovered from the beginning until the 3-month follow-up, and the interpersonal relationships with his deceased mother, his wife, colleague, and father changed after IPT. Case studies are inherently limited, but IPT, in consideration of Japanese cultural characteristics for bereavement-related MDD, can be potentially effective in Japan.